The Effectiveness of Fairy Tale Animation Video Media to Improve the Storytelling Ability of Children Aged 5-6 Years - Saputri, Nur Anis; ., Diana (Jurusan PGPAUD FIP UNNES, 2024)
The purpose of this research is to determine the effectiveness of fable fairy tale animation video media in improving the storytelling skills of children aged 5-6 years in Mekarsari Kindergarten. This study uses a quantitative approach, namely the type of experimental research with a one group pretest posttest design. The study population consisted of 30 children aged 5-6 years in Mekarsari Kindergarten. The sampling technique used the total sampling technique with all members of the population being sampled, namely children aged 5-6 years in Mekarsari Kindergarten with a total of 30 children. Data collection techniques using questionnaires and documentation. The data analysis technique uses inferential statistics by testing the hypothesis using the Paired Sample T-Test. The results of the research from the calculation of the t test obtained the value of tcount| > ttable, namely 26.543 > 2.04523, with a significance value of 0.000, so ?? is rejected and ?? is accepted, meaning that there is a significant increase in children's story telling ability of 35.27%. There is an average difference in the ability to tell stories before and after being given treatment. The N-gain test results obtained 0.58, thus indicating that the effectiveness of fable fairy tale animation video media to improve children's storytelling abilities is at the moderate level criteria as evidenced by the N-gain value can be obtained an average of 0.3 ≤ 0.58 ≤ 0 This shows that fable fable animation video media is effective in improving children's storytelling skills. Suggestions put forward in this study: (1) can make maximum use of fable fairy tale animation video media, (2) further researchers can develop fable fairy tale animation video media for other aspects. The purpose of this research is to determine the effectiveness of fable fairy tale animation video media in improving the storytelling skills of children aged 5-6 years in Mekarsari Kindergarten. This study uses a quantitative approach, namely the type of experimental research with a one group pretest posttest design. The study population consisted of 30 children aged 5-6 years in Mekarsari Kindergarten. The sampling technique used the total sampling technique with all members of the population being sampled, namely children aged 5-6 years in Mekarsari Kindergarten with a total of 30 children. Data collection techniques using questionnaires and documentation. The data analysis technique uses inferential statistics by testing the hypothesis using the Paired Sample T-Test. The results of the research from the calculation of the t test obtained the value of tcount| > ttable, namely 26.543 > 2.04523, with a significance value of 0.000, so ?? is rejected and ?? is accepted, meaning that there is a significant increase in children's story telling ability of 35.27%. There is an average difference in the ability to tell stories before and after being given treatment. The N-gain test results obtained 0.58, thus indicating that the effectiveness of fable fairy tale animation video media to improve children's storytelling abilities is at the moderate level criteria as evidenced by the N-gain value can be obtained an average of 0.3 ≤ 0.58 ≤ 0 This shows that fable fable animation video media is effective in improving children's storytelling skills. Suggestions put forward in this study: (1) can make maximum use of fable fairy tale animation video media, (2) further researchers can develop fable fairy tale animation video media for other aspects.